2003
DOI: 10.1300/j369v06n02_06
|View full text |Cite
|
Sign up to set email alerts
|

African American College Students' Preferences for Quick Service Restaurants

Abstract: The competition among the quick service restaurants (QSRs) continues to be intense, and college students have a variety of food choices to select. This study investigated the African American students' demographics, food habits, food preferences, and importance of image attributes in selecting and patronizing a QSR. The findings reveal that the four most important image attributes to this group of students seems to be: cleanliness, quality and taste of food/beverage, price/value, and friendly/attentive service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Related to high price sensitivity in the fast food restaurant industry (Carmin and Norkus, 1990), various studies confirmed the importance of perceived value (quality compared with price) to the formation of customer satisfaction (Khan, 2003;Terblanche and Boshoff, 2010). While the ECSI model contains only one perceived value construct (EPSI Rating, 2001, there is evidence that fast food restaurant customers separately relate product (food) quality and service quality to price (Brady et al, 2001;Lee and Ulgado, 1997).…”
Section: Fast Food Restaurantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Related to high price sensitivity in the fast food restaurant industry (Carmin and Norkus, 1990), various studies confirmed the importance of perceived value (quality compared with price) to the formation of customer satisfaction (Khan, 2003;Terblanche and Boshoff, 2010). While the ECSI model contains only one perceived value construct (EPSI Rating, 2001, there is evidence that fast food restaurant customers separately relate product (food) quality and service quality to price (Brady et al, 2001;Lee and Ulgado, 1997).…”
Section: Fast Food Restaurantsmentioning
confidence: 99%
“…Specifically, product (food) quality was shown to be the most influential antecedent to customer satisfaction with fast food restaurants in most countries (Clark and Wood, 1998;Keillor et al, 2004;Khan, 2003;Turner and Collison, 1988). While service quality has many facets, studies on fast food restaurants confirmed that these facets can be validly integrated into one construct (Chen and Chen, 2010;Khan, 2003;Lee and Ulgado, 1997;Qin et al, 2010;Terblanche and Boshoff, 2010).…”
Section: Fast Food Restaurantsmentioning
confidence: 99%
See 2 more Smart Citations
“…These features are secondary or complementary characteristics, and reliability or reliability, namely the smallest possibility of damage or failure when used (Lutfie et al 2015). Khan et al (2016) revealed that product quality relates to individual loyalty to buy an item. Research by Lutfie et al (2015) found that product quality influences Muslim women's decisions to buy Wardah products and halal cosmetics.…”
Section: Cosmetic Quality and Intentionmentioning
confidence: 99%